STUDENTS’ SELF-ESTEEM, MOTIVATION, AND THEIR SPEAKING SKILL ACHIVEMENT: A CORRELATIONAL STUDY - molya jodi prasetyo (Language-Edu, 2020)
The purpose of the study is to find out whether the students’ self-esteem, students’ motivation correlate with their English spiking skill achievement in English Language teaching. For this study the researcher took a speaking class at second semester students of English Teaching Department in IAIN Madura of 2018/2019 as participants. The research instrument of this research, the researcher provided two kinds of instruments. They are questionnaires and documentation, with the sample which consists of 30 students. This research used the quantitative approach with a research design called correlation design. The finding of this research showed the result of significance value for students’ self-esteem, students` motivation, and speaking skill achievement is 0.000. It means that the significance value < 0.05, so Ha is accepted.  While based on the table interpretation, the coefficient correlation value is 0.865. It is between 0.800 – 1.000 in the interpretation correlation table. This value shows there is a strong correlation between students’ self-esteem, students’ motivation and their speaking skill achievement.